2007
DOI: 10.1086/520680
|View full text |Cite
|
Sign up to set email alerts
|

Acute Q Fever Hepatitis in Patients with and without Underlying Hepatitis B or C Virus Infection

Abstract: The clinical manifestations of acute Q fever hepatitis differ little in patients with and patients without underlying viral hepatitis, and replication of hepatitis virus is not influenced by acute Q fever hepatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 23 publications
2
15
0
1
Order By: Relevance
“…In Taiwan, hepatitis rather than pneumonia is the predominant presentation of acute Q fever [28,29]. In our previous study, although all of the cases of acute Q fever had hepatitis, 19% of them had abnormal chest x-ray findings, and 9.5% had unilateral and 9.5% bilateral infiltration [29].…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan, hepatitis rather than pneumonia is the predominant presentation of acute Q fever [28,29]. In our previous study, although all of the cases of acute Q fever had hepatitis, 19% of them had abnormal chest x-ray findings, and 9.5% had unilateral and 9.5% bilateral infiltration [29].…”
Section: Discussionmentioning
confidence: 99%
“…Infective endocarditis is the most common complication, particularly in immunocompromised patients, pregnant patients, or those with cardiovascular abnormalities [3]. With regard to symptomatic acute Q fever, a geographic difference is found between the two major clinical presentations with pneumonia predominant in Nova Scotia, Canada [4], Switzerland [1], the north of Spain [5], and the Netherlands [6], [7] and hepatitis predominant in France [8], the south of Spain [9], California [10], Ontario, Canada [11], and Taiwan [12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous retrospective studies revealed that hepatitis is the predominant presentation of acute Q fever in Taiwan [12], [22]. However, a selection bias might exist in which clinicians tend to order Q fever tests in febrile patients who present with hepatitis when no pneumonia is found on the chest-x ray.…”
Section: Introductionmentioning
confidence: 99%
“…Q fever is a notifiable disease and approximately 19,20 In this study, no participant had been informed of the possibility of chronic Q fever nor knew the rationale for follow-up, highlighting the importance of further education about Q fever among local physicians.…”
Section: Discussionmentioning
confidence: 99%